“Estudio metodológico para el desarrollo de microservicios, diseño de un prototipo”. - Guevara Naranjo, Christian Paúl (2021)
This project was based on a bibliographic review, which details the methodologies for the development and creation of microservices, through the use of agile practices such as iterative development - Incremental, user stories, among others. The bibliographic research found, it permitted to highlight the change that the software industry has had in question from other forms of implementation, making a comparison between the most used traditional architectures and the new ones based on microservices, the main objective was to analyze the methodological process that follows for the development micro services and getting a strategy that includes quality attributes in this development process. In addition, given the lack of knowledge in our environment and is being a trend that carries the future in the software development industry, another of the important results of this study was, the designing and elaboration of a prototype based on a microservices architecture, which has a set of characteristics and functionalities, which serve as a starting point for future researchers and designers, especially in the Information Systems Engineering career of the Technical University of Cotopaxi, and as a demonstrative tool of behavior, communication and work. of micro services in a performance application, in addition to the potential provided by the technological tools used to create this new type of application.